Site characteristics that determine the growth and productivity of teak (Tectona grandis L.f.) of young plantations in Guatemala - Vaides López, Edwin Estuardo (2019)
The study was conducted on teak plantations between 2.6 and 7 years of age. Site properties were evaluated around Guatemala for productivity, based on the average annual height and total volume increase. A total of 113 permanent monitoring plots (PMP) from the departments of El Petén, Alta Verapaz, Izabal, Zacapa, Suchitepéquez, Retalhuleu and Escuintla were studied. Physiographic, climatic, soil, and silvicultural characteristics which influence the growth and productivity for this species were also determined. MAI in total height (MAITOTH) and MAI in total volume (MAIVOL) was correlated with all dependent variables. The analysis was carried out using graphics by scattering plots and separation of quadrants to define critical levels. The sites with greater growth and productivity were found at elevations of less than 220 m.a.s.l., on slopes of less than 40%, landscapes flat to hilly, low to medium rocky surface, and non-flooded and well-drained areas. These sites also have an average annual temperature of around 26ºC, 1900-2850 mm average annual rainfall, soil pH greater than 5.5, base saturation percentage greater than 43% in the top soil (0 to 20 cm), and land with little or no compaction. On sites with a pH <5.5 in the same layer, the best growth and productivity values were observed on soil with acidity saturation <5% and soil calcium saturation >62%.